2013
DOI: 10.1038/nutd.2013.39
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of nutrition education added to internet-based information and exercise at the work place for weight loss in a racially diverse population of overweight women

Abstract: Objective:Obesity in the United States is highly prevalent, approaching 60% for black women. We investigated whether nutrition education sessions at the work place added to internet-based wellness information and exercise resources would facilitate weight and fat mass loss in a racially diverse population of overweight female employees.Methods:A total of 199 (average body mass index 33.9±6.3 kg m−2) nondiabetic women (57% black) at our institution were randomized to a 6-month program of either internet-based w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 45 publications
(56 reference statements)
1
33
0
Order By: Relevance
“…One of the reasons of nutrition problems in the world is the lack of nutrition knowledge and consequently inappropriate performance in this category, which causes problems such as malnutrition and various non-communicable diseases [6]. Carnie's study showed that training and nutrition advice to US obese black women has been effective in reducing their weight and has led to a change in their eating habits [26]. Mobasheri also reported that nutritional counseling and education has been effective in improving the nutritional status of adults [3].…”
Section: Resultsmentioning
confidence: 99%
“…One of the reasons of nutrition problems in the world is the lack of nutrition knowledge and consequently inappropriate performance in this category, which causes problems such as malnutrition and various non-communicable diseases [6]. Carnie's study showed that training and nutrition advice to US obese black women has been effective in reducing their weight and has led to a change in their eating habits [26]. Mobasheri also reported that nutritional counseling and education has been effective in improving the nutritional status of adults [3].…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies used a randomized controlled trial (RCT) design [37][38][39][40][41][42][43][44][45][46][47][48][49] and 10 studies used a non-randomized study design (Table 1). [50][51][52][53][54][55][56][57][58][59] Nine studies were conducted in the United States 37,40,42,43,47,52,53,55,56,58 and two in Brazil. 44,45 Studies were also conducted in Iran, 50 Tunisia, 54 Norway, 38,39 Ireland, 51 Sweden, 41 Japan, 59 Germany, 57 Singapore, 46 and the Netherlands.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…54 All male participants had dropped out of one intervention group by week 12 in a 40-week RCT with two intervention groups. 38,39 Two studies included only participants with a BMI above 25 kg/m 2 at baseline, 40,58 and 17 studies reported using convenience sampling during recruitment. [37][38][39][40]42,43,[45][46][47][48][49][50][51][52][53][54][55][56][57][58] Eight studies delivered PA interventions (n = 12 intervention arms), [37][38][39]44,45,47,[50][51][52] and 12 studies delivered mixed interventions (n = 14 intervention arms), [40][41][42][43]46,48,49,[53][54][55][56][57][58][59] that is, a combination of PA and diet in...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations